The Strategy of Taman Mini Indonesia Indah as an Educational Cultural Tourism Destination for Generation Z Students - Bramantya, Yoga Akbar (UI Scholars Hub, 2024)
The Merdeka Belajar Program is a new policy of the Ministry of Education and Culture of the Republic of Indonesia that provides students with the freedom to learn, pays attention to their natural talents, and gives teachers and students the freedom to innovate. This program is designed based on the needs and desires of students, and utilizes educational tourism objects as a means of learning. Taman Mini Indonesia Indah (TMII) is one of the educational tourism destinations that is suitable for learning about Indonesian culture and diversity through detailed miniatures. TMII displays miniature traditional houses from various provinces with the cultural characteristics of each province. TMII also provides various other facilities such as theaters, museums, and amusement parks. Through strategies involving technology and social media, TMII strives to be an interesting and modern place of learning for generation Z, with the aim of enriching their knowledge of Indonesia's cultural diversity and increasing public awareness of educational cultural heritage that is ideal to be part of the Merdeka Belajar program.